The role of physical activity during pregnancy and its impact on the course of labour and labor outcomes - a review of literature - Anna Krysińska; Antonina Drzewiecka; Artur Drzewiecki; Wiktor Korczak; Monika Gaszyńska; Maria Anna Madejska; Aleksandra Rudzka; Wojciech Falkowski; Weronika Woźniak; Jakub Magielski (Quality in Sport)
Introduction: Pregnancy is a transformative stage in a woman’s life, often accompanied by questions and concerns about the safety of both the mother and the developing child. Key aspects of daily life, including physical activity, diet, and work, are frequently scrutinized, with many misconceptions persisting about what constitutes a healthy pregnancy. However, scientific evidence consistently demonstrates that an active and healthy pregnancy benefits both maternal and neonatal outcomes.